Traumatic disclosures in the life stories of older Vietnam era veterans. Issue 10 (22nd June 2022) - Sager, Zachary; Nathan, Susan; Doherty, Kelly; Pless Kaiser, Anica; King, Katherine D.; Topor, David R.; Morrison, Nicholas R.; Moye, Jennifer
Abstract: Background: Eliciting life stories is an important component of person‐centered care that may aid in understanding how an individual's unique background and narrative impacts their health. Such life stories, especially when gathered from older military Veterans, may include traumatic events, raising the urgency that clinicians be prepared to provide care that is trauma‐informed and ensure Veteran's experiences are acknowledged and treated effectively. Methods: We examined the prevalence and type of potentially traumatic and/or adverse life events spontaneously shared by 231 older Veterans participating in a life story intervention while receiving care within the U.S. Veterans Health Administration system. Veteran life stories were extracted from the electronic medical record and deductive qualitative content analysis was used to code potentially traumatic or adverse life experiences based on a codebook adapted from the Brief Trauma Questionnaire and Adverse Childhood Experience questionnaire. Results: A majority (71.0%) of Veterans described at least one traumatic disclosure in their life story. Among narratives with a disclosure of any type, more than half (53.0%) included descriptions of combat trauma, 21.5% noted a history of life‐threatening illness, and 9.5% reported having been in a serious accident. Fewer noted adverse childhood experiences (19.5%). Conclusions: Elicitation of life stories among older Veterans may advance person‐centered care and life stories frequently include disclosure of potentially traumatic and/or adverse life events. These findings underscore the normative experience of traumatic events among older Veterans and highlight the importance of developing age‐sensitive trauma‐informed care competencies.